Characteristics of precursors responsible for bulk damage initiation in doubler KDP crystal at different wavelengths. (1st November 2017) - Zheng, YinBo; Ba, RongSheng; Zhou, XinDa; Ding, Lei; Li, Jie; Yuan, Jing; Xu, HongLei; Na, Jin; Li, YaJun; Yang, XiaoYu; Chen, Bo; Zheng, WanGuo
Highlights: The damage performances can divide into three groups depending on the wavelength. Bulk damage resistance is both wavelength and polarization dependent at 2ω and 3ω. Different species of precursors for damage initiation exist in KDP crystals. Dominating absorption mechanism differs for different polarization orientations. Abstract: The characteristics of precursors responsible for damage initiation in type I doubler KDP crystals are investigated by analyzing the density of bulk damage sites under different exposure wavelengths and fluences combinations. The experimental results point out that the precursors could be classified as 1ω/2ω precursors and 3ω precursors according to their distribution, while it is the same precursors that differ from each other over three different wavelengths according to their geometry shape, i.e., different criteria lead to different species. We also find that the ratio of absorption efficiency factors at 1064 nm to that at 532 nm is associated with the polarization orientation, which manifests the existence of different dominating absorption mechanisms responsible for bulk damage initiation in doubler KDP crystals for different polarization orientations.